2009
DOI: 10.1038/jp.2009.17
|View full text |Cite
|
Sign up to set email alerts
|

Parents' perception of the back-transport of very-low-birth-weight infants to community hospitals

Abstract: Objective: To characterize parents' perception of back-transport of verylow-birth-weight (VLBW) infants from a regional referral neonatal intensive care unit (RR-NICU) to a community hospital (CH) for convalescent care.Study Design: Mixed methods utilizing parental interview and medical record review.Result: Overall, 20% of parents selected the CH to which their child was transferred. Less than half of the parents wanted the transfer. Psychological comfort with the RR-NICU was the most frequently reported reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 12 publications
(19 reference statements)
0
23
0
3
Order By: Relevance
“…As in most qualitative studies, interview was the preferred data collection method of the primary researchers and took place through individual, focus group, or telephone interviews with a small number of participants. An exception to the small number was Donahue, Hussey‐Gardner, Sulpar, and Aucott () primary study. In a mixed‐methods study, they collected data through telephone interviews with more than 200 mothers.…”
Section: Resultsmentioning
confidence: 99%
“…As in most qualitative studies, interview was the preferred data collection method of the primary researchers and took place through individual, focus group, or telephone interviews with a small number of participants. An exception to the small number was Donahue, Hussey‐Gardner, Sulpar, and Aucott () primary study. In a mixed‐methods study, they collected data through telephone interviews with more than 200 mothers.…”
Section: Resultsmentioning
confidence: 99%
“…Recent data from 236 neonatal families at two East Coast hospitals found that less than 50% of families desired back-transport, because of their comfort with the caregiver team at the high-level hospital. 53 Consistent communication between the provider and family is a critical element to a smooth back-transport. 54 Most studies of back-transport suffer from the biased selection of patients chosen for back-transport, compared to those who remained at the specialty center until discharge.…”
Section: Types Of Regionalization Studies and Their Outcomesmentioning
confidence: 99%
“…Further, regionalized systems need a back-transport of patients to non-specialty hospitals after they have been stabilized and their condition improved. Parents or guardians may be reluctant to back-transport, because of their comfort and belief in the high level hospital19). However, if not supported by a re-distribution system, the referred hospital could become crowded with patients awaiting treatment.…”
Section: Regionalization Of Pediatric Emergency Carementioning
confidence: 99%